Pain Control and Chaplaincy in Aotearoa New Zealand - Carey, Lindsay B. (Journal of religion and health, 2014)
This paper summarizes the results of 100 New Zealand health care chaplains with regard to their involvement in issues concerning pain control within the New Zealand health care context. Both quantitative (via survey) and qualitative methods (in-depth interviewing) were utilized. The findings of this study indicated that approximately 52 % of surveyed hospital chaplains had provided some form of pastoral intervention directly to patients and/or their families dealing with issues concerning pain and that approximately 30 % of hospital chaplains had assisted clinical staff with issues concerning pain. NZ chaplaincy personnel involved in pain-related issues utilized a number of pastoral interventions to assist patients, their families and clinical staff. Differences of involvement between professionally stipended hospital chaplains and their volunteer chaplaincy assistants are noted, as are the perspectives of interviewed chaplains about their pastoral interventions with issues relating to pain. Some implications of this study with respect to chaplaincy utility, training and collaboration with clinical staff are noted, as are comparisons with international findings.